2015
DOI: 10.36076/ppj/2019.19.e671
|View full text |Cite
|
Sign up to set email alerts
|

Late Extrusion of an Implantable Pulse Generator of a Spinal Cord Stimulator

Abstract: The objective of this manuscript was to report a case of a patient with extruded pulse generator 3 years after implantation of a spinal cord stimulator system. With the increasing incidence of chronic pain, spinal cord stimulation (SCS) is becoming more commonly utilized by pain physicians. SCS is a generally safe intervention with minimal adverse effects; however, there are risks of complications which practitioners should be aware of prior to and after placement of the SCS. We present a case of a patient wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Unlike lead migration, IPG-related complications have rarely been reported. The majority of IPG-related revision surgeries pertain to IPG battery depletion, which, in the case of rechargeable IPGs, is easily remedied via recharging and seldom requires revision surgery (20)(21)(22)(30)(31)(32). It is important to make a distinction between complications and revision surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike lead migration, IPG-related complications have rarely been reported. The majority of IPG-related revision surgeries pertain to IPG battery depletion, which, in the case of rechargeable IPGs, is easily remedied via recharging and seldom requires revision surgery (20)(21)(22)(30)(31)(32). It is important to make a distinction between complications and revision surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported IPG-related complications, which include battery flipping, recharging difficulties, and pressure necrosis from prolonged sitting (22,30). However, this scarcity of literature on IPG-related complications can by no means be an accurate representation of the actual number of patients who have IPG-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their successes in alleviating the chronic pain, these devices have several limitations, which originated from the following features. Since IPGs are packaged by the metal, its volume and the weight are fairly bulky and heavy (i.e., the volume and the weight of the PrimeAdvanced are around 40 cm 3 and 70 g, respectively), leading to various complications after implantation as well as restriction in the implantation location (i.e., hip or abdomen) [4,13,19]. Since the location of the implanted IPG is distant away from the actual stimulation position, a long lead wire is required to connect the electrode and the IPG [13,17], which results in complicated surgery for making a tunnel under the skin and risk of infection of a widespread lead wire.…”
Section: Introductionmentioning
confidence: 99%